Investigating and Translating Formality in English Legal Texts into Arabic - Al-Dahwi, Sameer Salih Mahdi (Al-Adab Journal, 2021)
Legal language is an unusual type of language which raises the interest of many people. It is considered to be one of the discourses that prefer traditional styles and values. Moreover, using this language is confined to specific places and circumstances, namely, in a court or legal texts. Additionally, legal language is radically different from ordinary language in vocabulary, morphology, syntax, and semantics, in addition to other distinctive features. In fact, one of the predominant distinctive features of legal language is that it is a formal language. It is hypothesized that formality in English legal language is realized with different ways and at different levels. It is also hypothesized that what is formal in English is not necessarily formal in Arabic. In other words, formal expressions in English and Arabic are realized differently. The data in this study has been quoted from different authentic legal texts supplemented by the researcher’s renderings.